Refunction Family during Covid-19 Pandemic (Study among Students of Anthropology UGM) - Abubakar, Ali; Ulamy Alya, Nabila (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
Today, the family experiences dysfunction because their functions are taken over by the state and the market. Before the Industrial Revolution, most people still relied on their families and communities for food, shelter, education, and employment. New communication and transformation technologies enable markets and governments to pull people out of family security and enter the market as individuals. During the Covid-19 pandemic, the authors saw a tendency for the return of family functions that had been taken away by the state and the market. People are getting closer to their families, especially because of the effects of physical distancing rules by the state. So far there have been no studies that show in detail how a pandemic really influences family functioning. The authors tries to investigate the functions of families returning to work using the daily data of UGM Cultural Anthropology students collected in the Rural Studies class in Indonesia from 30 March 2020 to 29 April 2020. Findings show that family refunction occurred during the pandemic.